The French Frontier of Settlement in Louisiana : Some Observations on Cultural Change in Mamou Prairie - Gold, Gerald (Cahiers de géographie du Québec, 1979)
Changes in Cajun culture of the Southwestem Prairies of Louisiana can best be explained through the ethnohistorical study of pre-1952 cotton sharecropping communities, and the subsequent displacement of the tenant farmers to service centres. Isolation of the sharecroppers was culturally-reinforced by a strong egalitarian ideology. From this milieu, Cajun music emerged as a marker of an indigenous Louisiana francophone society. The decline of cotton cultivation reversed the demographic balance between countryside and village and favoured the emergence of merchant and service strata composed of former farmers. The new bourgeoisie sought means of cultural revival through the reinterpretation of rural culture in a town context. Using radio, newspapers and the strong external support of folk "purists" they selectively cultivated ethnic differences. French was strengthened in a public context even though it continued to decline in private and familial contexts.The response to this transformation differs among occupation groups. Retired sharecroppers in Mamou, the most "Cajun" in their everyday retention of "traditional" social and linguistic behaviour, are the least likely to advocate the survival of that culture and its transmission to another generation.